Fitotoxicidade na cultura do milho em resposta a subdoses de sulfometuron-methyl - Felisberto, P. A.C. [UNESP]; Felisberto, G. [UNESP]; Ramos, A. R. [UNESP]; Timossi, P. C. (FapUNIFESP (SciELO), 2017)
The use of ripeners has been a common practice in the sugarcane culture. The application of these products is often performed through aerial spraying, which increases the chances of drifting of the ripeners- molecules over the surrounding crops, such as maize. In order to study possible phytointoxication on maize caused by sulfometuron-methyl application, a field experiment was conducted to evaluate the effects of sulfometuron-methyl sub doses on maize when applied at the V4 and V8 development stages. The experiment was installed in a randomized block design with four replications. The treatments followed a 2 x 5 factor scheme, with the first factor corresponding to development stages of maize during which the ripener was applied (V4 and V8) and the second factor was related to sulfometuron-methyl sub doses (0; 0.45; 0.90; 1.35 and 1.80 g a.i. ha1). The maize crop showed phytotoxicity with the use of 0.45 g a.i. ha-1 of sulfometuron-methyl; it was more severe when the application occurred at the development stage V8, leading the plant to death at the highest used dose. Furthermore, it was also possible to observe negative changes in the morphological and production components of maize plants. The SYN 7G17 maize hybrid is highly susceptible to sulfometuron-methyl. The occurrence of sulfometuron-methyl deposits at higher doses or at different development stages of the crop may reflect more severe phytotoxic effects than the ones observed in this study.
Maize crop phytotoxicity in response to sub-doses of sulfometuron-methyl
Keywords: Ripener; Selectivity; Zea mays